Impact of everolimus plus calcineurin inhibitor on formation of non-HLA antibodies and graft outcomes in kidney transplant recipients: 12-month results from the ATHENA substudy - Philippe, Aurélie; Arns, Wolfgang; Ditt, Vanessa; Hauser, Ingeborg A.; Thaiss, Friedrich; Sommerer, Claudia; Suwelack, Barbara; Dragun, Duska; Hillen, Jan; Schiedel, Christiane; Elsässer, Anja; Nashan, Björn (Frontiers in Transplantation, 2023)
Background: Non-human leukocyte antigen (non-HLA) antibodies including antibodies targeting Angiotensin II type 1 (AT1R) and Endothelin-1 type A (ETAR) receptors represent a topic of interest in kidney transplantation (KTx). This exploratory substudy evaluated the impact of everolimus (EVR) or mycophenolic acid (MPA) in combination with tacrolimus (TAC) or cyclosporine A (CsA) in patients with preformed non-HLA antibodies, potentially associated rejections and/or their impact on renal function over 1 year. Methods: All eligible patients were randomized (1:1:1) before transplantation to receive either EVR/TAC, EVR/CsA, or MPA/TAC regimen. The effect of these regimens on the formation of non-HLA antibodies within one year post de novo KTx and the association with clinical events was evaluated descriptively in randomized (n=268) population. Results: At Month 12, in EVR/TAC group, higher incidence of patients negative for AT1R-and ETAR-antibodies (82.2% and 76.7%, respectively) was noted, whereas the incidence of AT1R-and ETAR-antibodies positivity (28.1% and 34.7%, respectively) was higher in the MPA/TAC group. Non-HLA antibodies had no influence on clinical outcomes in any treatment group and no graft loss or death was reported. Conclusions: The studied combinations of immunosuppressants were safe with no influence on clinical outcomes and suggested minimal exposure of calcineurin inhibitors for better patient management.